Influence of kinesiophobia on activity, function, and anxiety levels in patients with rheumatoid arthritis - Shang Xueying; You Yanli; Xu Wei; Zhang Lingling; Li Lili (Frontiers in Medicine)
BackgroundRheumatoid arthritis (RA) is a chronic autoimmune disorder that causes joint inflammation and affects quality of life. Appropriate physical activity can enhance joint function and lower cardiovascular disease risk. However, individuals with RA often have reduced physical activity levels, likely due to kinesiophobia, or fear of movement.AimThis study aimed to assess the prevalence of kinesiophobia among RA patients and its influence on functional impairment, physical activity, and pain-related anxiety.MethodsUsing a convenience sampling method, we surveyed 350 RA patients attending outpatient clinics in the rheumatology and immunology departments of three tertiary hospitals in Henan Province, China, from August 18 to September 1, 2023. Participants completed the Tampa Scale of Kinesiophobia (TSK), the Signals of Functional Impairment Scale (SOFI), the International Physical Activity Scale—Short Form (IPAQ-SF), and the Pain Anxiety Symptoms Scale-20 (PASS-20). The Disease Activity Score 28 (DAS28) was retrieved for each participant to assess disease activity in RA patients. Descriptive analysis, Chi-square tests, Spearman correlation, and multiple linear regression assessed factors influencing kinesiophobia, with significance set at p < 0.05.ResultsResults indicated that 70.86% of participants experienced kinesiophobia, which was positively correlated with functional impairment and pain-related anxiety, while inversely related to physical activity levels (p < 0.001). Regression analysis revealed that kinesiophobia was explained by 65.5% of the variance, with gender, education level, functional impairment, pain-related anxiety, and pain severity identified as significant predictors (p < 0.05).ConclusionThe findings suggest that RA patients exhibit a high prevalence of kinesiophobia, predominantly influenced by factors such as gender, lower educational attainment, increased pain levels, greater functional impairment, and pain-related anxiety. Notably, physical activity levels did not serve as a predictor of kinesiophobia in this cohort.